Role of the Nigerian Government in the implementation of New Partnership for Africa's Development objectives (2001-2010) - Mamman Saba, Abdulkadir (2013)
This study is an attempt to assess the response of the Nigerian Government to the New Partnership for Africa’s Development (NEPAD) in relations to the objectives of good governance, poverty reduction, and peace and security agenda from 2001 to 2010. In other words, how successful has Nigeria been in meeting the required standard of good governance as stipulated in by NEPAD in terms of poverty reduction, peace and security building. Two theories have been adopted in this study and they were the dependency theory ,and the failed state theory. The central argument of dependence theory is that the African economy is too dependent on the economies of other economies in the international systems to the extent that this is to some extent responsible for the continent’s economic underdevelopment. The failed state theory on the other hand argues that it is the country leaders’ lack of good stewardship that has been responsible for the pervasive poverty, insecurity, corruption and unemployment that the countries in the continent have been experiencing. The importance of this study lies in the fact that it assesses performance and therefore come out with possible recommendations on how these may help alleviate Nigeria’s socio-economic condition and in the process help to strengthen the implementation of NEPAD’s APRM objectives of good governance, poverty reduction, peace and security in Nigeria in particular and in the continent more generally. The findings of the study revealed that the Nigerian government had failed to fully implement NEPAD’s APRM objectives of good governance, poverty reduction, peace and security programmes since the latter’s inception in Nigeria in 2001. The results of the study also showed that the greatest challenge of NEPAD’s APRM in Nigeria is the leadership issue. From the study, it was found that, the government had failed to fully respond to NEPAD’s objectives of poverty reduction, peace and security and good governance agenda. The study also revealed that, NEPAD’s APRM is entrenched in corruption although this seems to be more endemic at the federal level. The study was based on data collected through in-depth interviewing and focus group discussion (FGD). In the study, both primary and secondary sources of data were used. Primary data were collected through interviews and focus group discussion obtained from the field work. The secondary data were obtained from books, journals and reports. In analyzing these data, a systematic qualitative approach was adopted. The analysis of the data was carried out by transcribing the whole data collected through individual interview, focus group discussion and notes taken during the interview session. In conclusion, if NEPAD’s APRM is to remain viable, strong and reliable, a formidable and well defined policy engagement is required. It is also found that for NEPAD’s objectives to be fully implemented, commitment and political will of the leaders as well as adequate resources are needed. In addition, a strong legislation is required to prevent corrupt and abuse of power so that NEPAD’s APRM can be vigorously implemented. It is only when these recommendations are implemented can NEPAD’s APRM objectives of good governance, poverty reduction, peace and security be pursued for the betterment of Nigeria.